Indirect shoot regeneration from callus of the shoot tip explants of Gerbera jamesonii Bolus cv. "Festival" - Mahmood Shakir Hashim; Majid Abdulhameed Ibrahim (University of Thi-Qar Journal of agricultural research, 2024)
The study was conducted in the Tissue Culture Laboratory, Fadak Agricultural Company, Basrah, Iraq. Mother plants of the “Festival” gerbera cultivar were used for micropropagation by taking the shoot tip explants. The concentration of 2 mgL-1 benzyl adenine (BA) resulted in recording the highest percentage of response to callus induction, reaching 90%, which was significantly superior to the other two treatments, 1 and 1.5mgL-1 BA. The 1 mgL-1 BA treatment was significantly superior in response to indirect shoot generation when compared with the 1.5 and 2 mgL-1 BA treatments. The 1 mgL-1 BA treatment recorded the highest percentage of response to shoot growth induced by callus, which reached 100%. The treatment of callus grown in MS medium supplied with BA concentration of 1 mgL-1 recorded the highest average number of shoots, which reached 10 shoots per 50 mg of callus. The MS medium treatment supplied with a concentration of 0.5 mgL-1 of naphthalene acetic acid (NAA) was significantly superior to the other two treatments of 1 and 1.5 mgL-1 NAA in the percentage of shoot response to root formation. The concentration of 0.5mgL-1 NAA recorded the highest response to root formation, which reached 100%. The treatment of the MS medium supplied with a concentration of 0.5 mgL-1 NAA was significantly superior to the treatments of 1 and 1.5 mgL-1 NAA in the average number of main roots formed on the shoots. This treatment recorded the highest average of main roots, amounting to 3.2 main roots shoot-1.Callus, cultivar, indirect shoot, micropropagation, proliferation, MS salts.